How predator functional responses and Allee effects in prey affect the paradox of enrichment and population collapses - Boukal, David S; Sabelis, Maurice W; Berec, Ludek (Theoretical population biology, 2007)
In Rosenzweig-MacArthur models of predator-prey dynamics, Allee effects in prey usually destabilize interior equilibria and can suppress or enhance limit cycles typical of the paradox of enrichment. We re-evaluate these conclusions through a complete classification of a wide range of Allee effects in prey and predator's functional response shapes. We show that abrupt and deterministic system collapses not preceded by fluctuating predator-prey dynamics occur for sufficiently steep type III functional responses and strong Allee effects (with unstable lower equilibrium in prey dynamics). This phenomenon arises as type III functional responses greatly reduce cyclic dynamics and strong Allee effects promote deterministic collapses. These collapses occur with decreasing predator mortality and/or increasing susceptibility of the prey to fall below the threshold Allee density (e.g. due to increased carrying capacity or the Allee threshold itself). On the other hand, weak Allee effects (without unstable equilibrium in prey dynamics) enlarge the range of carrying capacities for which the cycles occur if predators exhibit decelerating functional responses. We discuss the results in the light of conservation strategies, eradication of alien species, and successful introduction of biocontrol agents.
Keywords: Models, Statistical; predátorské chování; Ecosystem; statistické modely; populační dynamika; Models, Biological; hustota populace; Predatory Behavior; mortalita; Animals; Mortality; Population Density; Population Dynamics; zvířata; ekosystém; biologické modely